1994
DOI: 10.1161/01.atv.14.4.636
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow on the process of endothelial cell division.

Abstract: In this study we investigated the effect of flow and the associated shear stress on the process of endothelial cell division. A shear stress of 7 N/m 2 (70 dyne/cm 2 ) was applied to a monolayer of bovine aortic endothelial cells (BAECs) by using a parallel-plate flow-chamber system. Dividing cells under flow conditions were qualitatively compared with those under static-culture conditions. In addition, the duration of some phases of the cell cycle (ie, mitosis and cytokinesis) was measured for both static and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 22 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…The onset of apoptosis due to flow disturbances may constitute the leading stimulus in initiation of atherosclerosis. It has also been shown that the nature of hemodynamic flow influences the proliferative status of vascular endothelium (19). There are numerous descriptions of atherosclerotic lesions in areas of disturbed flow (17, 18, 20 -24, 24 -28).…”
Section: Discussionmentioning
confidence: 99%
“…The onset of apoptosis due to flow disturbances may constitute the leading stimulus in initiation of atherosclerosis. It has also been shown that the nature of hemodynamic flow influences the proliferative status of vascular endothelium (19). There are numerous descriptions of atherosclerotic lesions in areas of disturbed flow (17, 18, 20 -24, 24 -28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this nonphysiological culture condition may accelerate endothelial dedifferentiation and further enhance the loss of the BBB characteristics with serial cell passage (e.g., cellular polarity determined by the functional specialization of the apical and basolateral membranes) 57. The lack of antimitotic influences by laminin and flow shorten the life span of the endothelium and cause ECs to grow uncontrolled in a multilayer fashion141,142 when cells start dedifferentiating. ECs grown in Transwell tend to have irregular patterns of cell adhesion, which prompt the so‐called “edge effect.” This term refers to a condition wherein the inability to form proper tight junctions between adjacent cells and between the endothelium alongside the perimeter of the membrane and the inner wall of the luminal chamber leads to artifactual paracellular diffusion, thus affecting the reliability of permeability measurements across the endothelial monolayer.…”
Section: Static Models Of the Bbb: Ec Monoculturesmentioning
confidence: 99%
“…The mechanotransduction effects of shear stress are believed to mediate several cellular functions, including the inhibition of cellular proliferation by the activation of p53 expression with the potential of arresting endothelial cell apoptosis . Furthermore, in the absence of laminar flow, static monolayers can be subject to uncontrolled growth, resulting in formation of multiple layers, if allowed to proliferate . Therefore, a model with the ability to incorporate physiologically relevant shear stresses is essential to effectively capture biologically relevant transport across any barrier in direct contact with the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…46 Furthermore, in the absence of laminar flow, static monolayers can be subject to uncontrolled growth, resulting in formation of multiple layers, if allowed to proliferate. 47 Therefore, a model with the ability to incorporate physiologically relevant shear stresses is essential to effectively capture biologically relevant transport across any barrier in direct contact with the bloodstream. Additional limitations of existing models to probe human brain permeability include the use of rodent brain endothelial cells, 36,40 which do not exhibit the same anatomical and molecular complexities as their human counterparts.…”
Section: Introductionmentioning
confidence: 99%